Bulbar Conjunctival Thickness in Eyes with Pseudoexfoliation Measured by Anterior Segment OCT - Mahla Shadravan; Shahin Yazdani; Bahareh Kheiri; Farideh Sharifipour; Azadeh Doozandeh; Mohammad Mehdi Hatami; Neda Einollahi (Journal of Ophthalmic & Vision Research)
Purpose: Eyes with pseudoexfoliation demonstrate fragile intraocular structures. The current study evaluated conjunctival thickness in pseudoexfoliation eyes as compared to a control group. Methods: In this cross-sectional study, patients with pseudoexfoliation and an age-matched control group underwent measurement of bulbar conjunctival thickness in the superior and temporal quadrants, 1, 2, and 3 mm posterior to the limbus using anterior segment OCT. Results: A total of 140 eyes of 140 subjects including 68 eyes of 68 patients with pseudoexfoliation and 72 eyes of 72 control subjects without pseudoexfoliation were studied. Both study groups were divided into two subgroups – those using glaucoma drops versus medication-free eyes. Total conjunctival thickness in pseudoexfoliation eyes was significantly lower than control eyes across all comparisons. Conjunctival thickness in the superior quadrant 1, 2, and 3 mm from the limbus was 177.62 ± 41.30, 235 ± 48.41, and 231.40 ± 49.81 μm, respectively in the pseudoexfoliation group versus 207.49 ± 48.92, 265.67 ± 52.66, and 262.74 ± 59.43 μm in the control group (P <0.001, <0.001, and 0.001, respectively). In the temporal quadrant, conjunctival thickness 1, 2, and 3 mm from the limbus was 193.62 ± 46.97, 198.19 ± 54.67, and 178.59 ± 57.90 μm, respectively in the pseudoexfoliation group versus 213.76 ± 47.06, 224.50 ± 56.24, and 210.26 ± 63.70 μm in the control group (P = 0.012, 0.006, and 0.003, respectively). Conclusion: Conjunctival thickness was significantly less in pseudoexfoliation eyes than an age-matched control group which supports clinical observations of thinner and more fragile conjunctiva in these eyes with implications for glaucoma surgery.